Evaluation of three varieties of Megathyrsus maximus in the dry period - Fortes, Dayleni; Valencia, Daiky; García, C. R.; García, M.; Cruz, Ana M.; Romero, Aida (Cuban Journal of Agricultural Science, 2016)
To characterize morphoagronomical and quality indicators of Megathyrsus maximus cv. Likoni, Mombaza and Tanzania in the dry period, a random block design with five replications and three treatments which corresponding to the studied varieties was used. Plots of 5x7 m were sown and the cutting height was of 10 cm above soil level. The study was developed during two consecutive years. The determined indictors were: dry matter content of thewhole plant, height, dry matter yield, morphological composition, length and width of leaves, number of tillers and number of plants/m2. The quality indicators of plants were also analyzed: crude protein, neutral detergent fiber and acid detergent fiber. Mombaza and Tanzania had the highest yields (P < 0.001) during the first year, with values of 3.84 and 3.94 t/ha, respectively, while Likoni and Tanzania showed the highest yields(P < 0.001) in thesecond year (2.49 and 2.46 t/ha, respectively). The Likoni variety showed the lower (P < 0.001) leaves percentage (65.42 % and 67.84 %) and higher (P < 0.001) of stems (34.58 % and 20.47 %) during the first and second year, respectively. The quality indicators: crude protein, EE, neutral detergent fiber, acid detergent fiber, lignin, cellulose, hemicelluloses and in vitro dry matter digestibility showed no differences between varieties. It is concluded that theplants studied had an adequate agroproductive performance under the edphoclimatic and management conditions in which the study was carried out. The Mombaza and Tanzania varieties are a good option to counteract the lack of food in the dry period because of its higher leaves proportion, which provides a higher quality to the food.Key words: Megathyrsus, quality, morphoagronomical performance,dry period